"We are survivors and not a virus:" Content analysis of media reporting on Ebola survivors in Liberia. - Elisabeth Anne-Sophie Mayrhuber; Thomas Niederkrotenthaler; Ruth Kutalek (Public Library of Science (PLoS), 2017)
The Ebola virus disease epidemic between 2013 and 2016 in West Africa was unprecedented. It resulted in approximately 28.000 cases and 10.000 Ebola survivors. Many survivors face social, economic and health-related predicaments and media reporting is crucially important in infectious disease outbreaks. However, there is little research on reporting of the social situation of Ebola survivors in Liberia.The study used a mixed methods approach and analysed media reports from the Liberian Daily Observer (DOL), a daily newspaper available online in English. We were interested to know how the situation of Ebola survivors was portrayed; in what way issues such as stigma and discrimination were addressed; and which stigma reduction interventions were covered and how. We included all articles on the situation of Ebola survivors in the quantitative and in-depth qualitative analysis published between April 2014 and March 2016.The DOL published 148 articles that portrayed the social situation of Ebola survivors between the 24 months observation period. In these articles, Ebola survivors were often defined beyond biological terms, reflecting on a broader social definition of survivorship. Survivorship was associated with challenges such as suffering from after-effects, social and economic consequences and psychological distress. Almost 50% of the articles explicitly mentioned stigmatisation in their reporting on Ebola survivors. This was contextualised in untrustworthiness towards international responses and the local health care system and inconclusive knowledge on cures and transmission routes. In the majority of DOL articles stigma reduction and engaging survivors in the response was reported as crucially important.Reporting in the DOL was educational-didactical and well-balanced in terms of disseminating available medical knowledge and reflecting the social situation of Ebola survivors. While the articles contextualised factors contributing to stigmatisation throughout the reporting, journalistic scrutiny regarding effectiveness of interventions by government and NGOs was missing.